OSTEOSARKOMA DIAGNOSIS DAN PENANGANANNYA - Kawiyana, Siki (journal of internal medicine; Vol. 10, No. 1 Januari 2009, 2012)
Osteosarcoma is the second most common bone malignant neoplasm. Occurs between 5 Ð 30 years old, most often between 10 Ð 20 years old. It is located at long bone metaphyses which has rapid growth rate, therefore it is most often found in the knee. Its diagnosis is established based on clinical findings, laboratory examination, radiographic examination such as plain xray photo, CT-scan, MRI, bone scan, angiography and biopsy histopathologic examination. The osteosarcoma prognosis depends on its stage and treatment effectivity. The osteosarcoma currently is managed by giving chemotherapy at pre-operative (induction=neoadjuvant chemotherapy) and post-operative (adjuvant chemotherapy). ÓLimb salvageÓ is the expected objective in surgical treatment for osteosarcoma. Post-operative follow up is very crucial in managing patient with osteosarcoma.
Keywords: Osteosarcoma, diagnosis, treatment